2018
DOI: 10.1128/jvi.00095-18
|View full text |Cite
|
Sign up to set email alerts
|

Antigenically Diverse Swine Origin H1N1 Variant Influenza Viruses Exhibit Differential Ferret Pathogenesis and Transmission Phenotypes

Abstract: Influenza A(H1) viruses circulating in swine represent an emerging virus threat, as zoonotic infections occur sporadically following exposure to swine. A fatal infection caused by an H1N1 variant (H1N1v) virus was detected in a patient with reported exposure to swine and who presented with pneumonia, respiratory failure, and cardiac arrest. To understand the genetic and phenotypic characteristics of the virus, genome sequence analysis, antigenic characterization, and ferret pathogenesis and transmissibility ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 45 publications
(48 reference statements)
6
46
0
Order By: Relevance
“…In contrast, in 2017-2018 a drifted H3N2 predominated for which the vaccine was not efficacious, but individuals aged 5-24 had the lowest number of infections in that year (2) and would include a large number of individuals imprinted with H1N1pdm09 virus. Previous studies in ferrets have also demonstrated that pre-existing H1N1pdm09 immunity 31 days prior allowed for rapid clearance of an antigenically distinct swine influenza virus and demonstrated reduced disease severity compared to naïve ferrets (39). Our data support this idea as immune imprinting with H1N1pdm09 is superior to H3N2 imprinting to protect from infection with heterologous viruses.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, in 2017-2018 a drifted H3N2 predominated for which the vaccine was not efficacious, but individuals aged 5-24 had the lowest number of infections in that year (2) and would include a large number of individuals imprinted with H1N1pdm09 virus. Previous studies in ferrets have also demonstrated that pre-existing H1N1pdm09 immunity 31 days prior allowed for rapid clearance of an antigenically distinct swine influenza virus and demonstrated reduced disease severity compared to naïve ferrets (39). Our data support this idea as immune imprinting with H1N1pdm09 is superior to H3N2 imprinting to protect from infection with heterologous viruses.…”
Section: Discussionsupporting
confidence: 83%
“…There may be specific virus properties that conferred a better "fit" for the H3N2v to infect humans; in fact, H3N2v viruses from 2009-2011 and 2011-2016 were capable of airborne transmission in ferrets (Pearce et al 2012;Sun et al 2018), the standard animal model used to assess mammalian transmissibility of influenza viruses. However, human H1v viruses were also shown to successfully infect and transmit between ferrets (Pulit-Penaloza et al 2018a,b, 2019a. Moreover, some swine IAV have been shown to infect and transmit among ferrets without evidence of human zoonosis (Yen et al 2011;Zhu et al 2011;Pascua et al 2012Pascua et al , 2013.…”
Section: Risk Of Contemporary Swine Iav For Humansmentioning
confidence: 99%
“…This diversity and the human-swine interface are incredibly important in the context of variant IAV infections in humans. Dramatic increases in the detection of variant IAV infections began with H3N2 viruses in the United States in 2012 (Epperson et al 2013), and these viruses are regularly detected in the United States (Jhung et al 2013;Choi et al 2015;Greenbaum et al 2015;Duwell et al 2018;Pulit-Penaloza et al 2018a) and to a lesser degree in other countries (Resende et al 2017;Xie et al 2018;Lu et al 2019). The risk of variant infection is likely dependent on animal production systems, animal-human interfaces (e.g., live animal markets, exhibition practices), the ecology of the virus, and other less tangible factors (Karesh et al 2012).…”
mentioning
confidence: 99%
“…Especially in infants, young children, pregnant women, the elderly, and patients with weakened immune systems, influenza is likely to cause serious complications; therefore, the World Health Organization (WHO) has identified influenza as a major public health problem 3,4 . Furthermore, emergence and spread of new high pathogenic influenza variants have posed a critical challenges to the global health and include swine-origin H1N1, H5N8, H9N2, and H7N9 [5][6][7][8] . In China, a novel H7N9 avian influenza virus caused 5 nationwide outbreaks from January 2013 to June 2017 9 .…”
mentioning
confidence: 99%